P53 Study protocol for a randomized controlled trial on the effectiveness of advance care planning (ACP) in general practice. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Stevens, J; de Vleminck, A; Pype, P; Deliens, L; Pardon, K
Abstract : Background: General practice is an optimal setting for ensuring timely initiation of ACP discussions. A multi-component ACP intervention developed for the general practice setting, aimed at patients with chronic life-limiting illnesses and their general practitioner, has been pilot tested. The aim of this study is to evaluate the effectiveness of this intervention and to evaluate its implementation by means of a process evaluation. Methods/Design: Using a cluster-randomized controlled trial (RCT) (randomization at the practitioner level, n=53 practitioners per condition, n=133 patients per condition), we will compare the structured ACP communication intervention to usual care, employing baseline measures (T0), and follow-up at 6 months (T1) and 12 months post-baseline (T2). Primary endpoints are quality of communication about end-of-life care and concordance between patients' preferences and received care at the end of life (as reported by the family caregiver if the patient died). Other patient or caregiver-reported outcomes include health-related quality of life, anxiety and depression, quality of end-of-life care, and quality of death and dying. Following the RE-AIM framework, structured diaries for trainers and general practitioners, as well as qualitative interviews with general practitioners, patients and family caregivers are among the measures used for the process evaluation. Discussion: After this Phase III RCT, we will be able to present a well-tested and evaluated ACP intervention that can be implemented in general practice. The results of the process evaluation will provide insight needed to allow adaptation of the intervention for a greater variety of national and international contexts.